Human capability evaluation approach for cybersecurity in critical industrial infrastructure - Ani, Uchenna P.; He, Hongmei; Tiwari, Ashutosh (Springer, 2016)
Every organization is as frail as its frailest human link in the cyber security of Industry Control System (ICS), which is without predisposition to conceivable technological solutions for enforcing security. Noticeably, human-involved systems are becoming more chaotic, and gravely under attacks due to irregular actions or inactions of human entities in the constituent chain. Many industrial cyber-attacks have successfully defeated technological security solutions through preying on human weaknesses in knowledge and skills, and manipulating insiders within organizations into unsuspectingly delivering entry and access to sensitive industrial assets. In order to help enterprises assess the level of employees’ cyber security awareness and responsiveness, and enhance ICS Cyber security knowledge and skills for ICS protection, a Workforce Cyber Security Capability evaluation model is presented, and theoretically validated. A capability evaluation will allow industries to have a better understanding of the potential state of consciousness, readiness and diagnostic abilities of the industries; thus improve the prevention, detection, and response to any cyber-specific incidents.
Keywords: Workforce-centred evaluation; – Workforce security evaluation; Industrial security evaluation; Cyber security evaluation; Human-centred vulnerabilities